2022
DOI: 10.1186/s12891-022-05111-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adipokines gene polymorphisms and knee osteoarthritis: a meta-analysis

Abstract: Background Adipokines gene polymorphisms are speculated to be associated with the risk of knee osteoarthritis (OA), but evidence remains conflicting. This study therefore aimed to examine whether associations exist between adipokines gene polymorphisms and knee OA by considering the evidence collected from eligible studies through a meta-analysis. Methods A systematic search was performed on PubMed, Embase, Web of Science, China National Knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The association was observed in gene LEPR 1,137,101. Additionally, limited data revealed that associations may also exist in ADIPOQ rs2241766, VISFATIN rs4730153 and VISFATIN rs16872158 [23]. The relationship between obesity and the prevalence of KOA has been confirmed by a number of studies, in which it was indicated that obesity contributes to an increase in the load on the joint, the development of an inflammatory response, negative consequences in the body and lifestyle change in favor of reducing physical activity [16].…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…The association was observed in gene LEPR 1,137,101. Additionally, limited data revealed that associations may also exist in ADIPOQ rs2241766, VISFATIN rs4730153 and VISFATIN rs16872158 [23]. The relationship between obesity and the prevalence of KOA has been confirmed by a number of studies, in which it was indicated that obesity contributes to an increase in the load on the joint, the development of an inflammatory response, negative consequences in the body and lifestyle change in favor of reducing physical activity [16].…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…In adult and pediatric Latin populations, particularly among Mexican people, the highest frequencies of obesity worldwide have been observed 8 . Obesity is a risk factor for OA not only through the action of mechanical forces that overload the joints but also due to a variety of metabolically active adipokines that play a role as mediators of inflammation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The association between OA and metabolic syndrome is now well established, but also emerging is the shared genetic basis between OA and conditions such as obesity and major depressive disorder. 30 , 31 , 34 Furthermore, our knowledge of the interplay between the gut microbiome, the environment, and OA is rapidly evolving. The collection of trillions of microbial organisms that reside in the gastrointestinal tract has been shown to play a key role in host metabolism, the immune system, and inflammatory response.…”
mentioning
confidence: 99%